Selecting (or not) physical education as an elective subject: Spanish high school students' views - Fenandez-Rio, Javier; García, Salvador; Ferriz-Valero, Alberto (Physical education and sport pedagogy, 2025)
The interactions between behavior, environment and personal factors are the basis of the Social Cognitive Theory (Bandura, A. 1986. Social Foundations of Thought and Action. NJ: Prentice Halls). Within this theory, students' behavior and motivation toward an activity is dependent on their feelings, thoughts and beliefs (Lodewyck and Pybus 2013. "Investigating Factors in the Retention of Students in High School Physical Education." Journal of Teaching in Physical Education 32 (1): 61-77). Physical education can provide attractive contexts to promote students' learning, but this depends on the teachers' ability to offer them relevant educational experiences (Bailey, R. 2018. "Sport, Physical Education and Educational Worth." Educational Review 70 (1): 51-66). Meaningful physical education is a pedagogical approach whose aim is to help teachers design significant experiences for all students (Beni, S., T. Fletcher, and D. Ní Chróinín. 2022. "'It's not a Linear Thing; There are a Lot of Intersecting Circles': Factors Influencing Teachers' Implementation of Meaningful Physical Education." Teaching and Teacher Education 117: 103806). Physical education is a compulsory subject in Spain, but it is not included in the final year of high school. In 2018, one autonomous community decided to offer it as an elective subject in this course. Scholars and institutions claim for more hours of physical education. But, what about the students? Do they really want more? The goal of the present study was to uncover the reasons why students selected, or not, physical education when it was included as an elective subject in their final year of high school. A total of 795 year-13 students (17-18 years), enrolled in 13 different high schools participated. 444 (55.8%) had not selected physical education (61.71% females), while 351 (44.2%) did selected it (44.44% females). Convenience sampling was used to include participants, considering the possibilities of the researchers to access them. The study followed an ex post facto, transversal, prospective research design to gather data in a single time point (Cohen, L., K. Manion, and K. Morrison. 2011. Research Methods in Education. Routledge). Within this framework, a qualitative research design was selected to obtain rich, detailed, and heavily contextualized information from the source (Creswell, J. W. 2013. Qualitative Inquiry and Research Design: Choosing among Five Approaches. Sage). The participants responded to an open-ended question 3-4 weeks after the beginning of the school year to 'fully explain the reason(s) for (not) selecting physical education in the final year of high school'. The qualitative software package MAXQDA 11 was used to help with data administration. The deep analysis of the participants' responses produced five themes for not selecting physical education (from strong to weak): academic stress, negative experiences, out-of-school physical activity, timetable, and importance, and four themes for selecting it: grade point average, importance, sport, and positive experiences. Results indicate that many students would eliminate physical education from their timetables if they had the chance. In many cases, it does not provide meaningful experiences, which produces low domain value. If physical education wants to survive as an academic subject in the schools, it must listen to its students, and attend their demands.